A privacy-preserving e-participation framework allowing citizen opinion analysis. (2015) - Buccafurri, Francesco; Fotia, Lidia; Lax, Gianluca
In e-democracy, e-participation represents a key component, as it is the way to adapt government decisions to the real expectations of citizens. The availability of information-communication technologies represents the basis for the implementation of concrete plans of citizens' participation to the government of the community. However, there is a non trivial trade-off to manage, between security and privacy needs and opinion analysis opportunities. Indeed, whereas we have to guarantee that the action of citizens is kept anonymous, relating opinions to information about people allows the government management to coherently orient the executive action. In this paper, we present a solution of the above trade-off, by proposing a framework relying on existing social networks and working through cryptographic protocols able to ensure citizens' anonymity yet enabling opinion analysis. A careful security analysis and the addressing of the main implementation issues make the proposal ready to a secure and feasible adoption in real-life contexts.